Alginate encapsulation technology of bacteria for promising self-healing concrete - Mauludin Luthfi Muhammad; Susanto Ambar; Keryanti; Widiarnoko Gandhi; Hafizh Muhammad (E3S Web of Conferences, 2024)
Concrete is a material that is often used in construction in Indonesia. Concrete has the disadvantage that it tends to form cracks. The cracks that form start from small cracks and then enlarge, causing a decrease in quality. Self-healing concrete is a type of concrete that could repair itself with the help of healing agents in the form of bacteria. There are several methods of mixing bacteria into concrete, one of which is by mixing bacteria directly or using a shell which is often called encapsulation. The purpose of this study was to analyze the behavior of the addition of Bacillus Megaterium bacterial encapsulation in terms of compressive strength of concrete with encapsulation proportions of 0%, 2% and 4% by volume weight and using alginate-based shells. The samples used were 15 x 30 cm cylindrical specimens. These specimens were then tested after 7 days and 28 days. Based on test result, it was found that the highest compressive strength was obtained when 2% alginate capsules were added on day 7 and day 28, namely 25.6 MPa and 32.2 MPa. Concrete begun to heal after 2 weeks of curing based on visual observation.